Internship report at the Virtual Reality Unit of the International Comittee of the Red Cross (ICRC) - Moreno Rodas, Jonathan (My University, 2020)
This report describes, through the selection of representative projects, the work developed by trainee Jonathan Moreno Rodas, during the curricular internship held at the Virtual Reality Unit of the ICRC in Bangkok, under the master’s degree in Design and Visual Culture at IADE. The theoretical framework consists of a literature review based on the concepts of storyboarding, illustration, animation and graphic design to complement the description of the work developed during the internship. As result of this experience the trainee was able to develop and strengthen design skills as well as animation, drawing synthesis, storyboarding and problem-solving abilities with pre-established deadlines.
Keywords: Illustration; Animation; Storyboarding; Graphic Design; Script; Illustration techniques; Video tutorials; Intership report